Thermodynamic maximum of Y doping level in barium zirconate in co-sintering with NiO. Issue 12 (11th March 2019) - Ueno, Katsuhiro; Hatada, Naoyuki; Han, Donglin; Uda, Tetsuya
Abstract : 2 phase equilibrium of Y-doped BaZrO3 and NiO is only achievable when the doping level is less than 12 mol%. Abstract : Y-doped barium zirconate (BZY) is a candidate electrolyte for the next generation fuel cells, and nickel (Ni) is known to be an excellent and cost-effective catalyst for high-temperature fuel cells. The conductivity of BZY increases with the Y content up to around a 20 mol% doping level. Therefore, 20 mol% Y-doped barium zirconate (BZY20) and NiO are the best-matched candidates if BZY20 can function with NiO in equilibrium at the fabrication temperature. We revealed the compatibility between BZY20 and NiO by establishing the critical parts of the phase diagram for the BaO–ZrO2 –Y2 O3 –NiO system at 1500 °C. With this knowledge, it was found that a 2 phase equilibrium of BZY and NiO is achievable only when the Y doping level in barium zirconate, defined as the molar ratio of Y/(Zr + Y), is less than 12 mol%, which means that the 2 phase equilibrium of BZY20 and NiO cannot be achieved at 1500 °C. This indicates that the conventional co-sintering process of the BZY20 electrolyte and the NiO anode causes a decrease in the Y doping level in barium zirconate and the conductivity of the electrolyte. BZY20 electrolyte-based fuel cells co-sintered with NiO anode, therefore, show lower performance than expected from the protonic conduction of pure BZY20, though many research groups adopt the co-sintering process.